Funerary Spells at Saqqara South: Some Considerations about the Inscriptions of Anu’s Coffin (Sq20X) and their Date - Russo, Barbara (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
This article concerns burial equipment found intact at Saqqara South in 1935. The owner, Anu, reused an annex of an Old Kingdom mastaba; his equipment included two inscribed coffins, one of which is no longer preserved. The case of this official is noteworthy, since it documents the mortuary traditions of the “spells of Nut”, derived from the Pyramid Texts and further manipulated after the end of the Old Kingdom. The detailed study of this inscription on Sq20X, Anu’s inner coffin, sheds light on the links with other Middle Kingdom sources (particularly S1C, Da1C, Da2–4X). Moreover, the archaeological, prosopographical and textual data have been integrated to propose a probable date for this official at the very end of the Eleventh or early Twelfth Dynasties.